Acute Caffeine Intake Reduces Perceived Exertion But Not Muscle Pain during Moderate Intensity Cycling Exercise in Women with Fibromyalgia. Issue 7 (3rd October 2022) - Schamne, Julio Cezar; Ressetti, Juliana Campos; Bertuzzi, Romulo; Okuno, Nilo Massaru; Lima-Silva, Adriano Eduardo
Abstract: Objective: Exacerbated perceived exertion and muscle pain responses during exercise might limit physical activity practice in fibromyalgia patients. Thus, nutritional strategies that can reduce perceived exertion and muscle pain during exercise in fibromyalgia patients would be useful. The purpose of this study was to investigate the effects of acute caffeine intake on the perceptions of exertion and muscle pain during a moderate intensity exercise in women with fibromyalgia. Method: Using a randomized, double-blinded, placebo-controlled and crossover experimental design, eleven sedentary women diagnosed with fibromyalgia (age: 44.6 ± 10.5 years; body mass index: 28.5 ± 4.5 kg.m −2 ) ingested a capsule containing either caffeine (5 mg per kg of body mass) or cellulose (placebo), 60 minutes before performing a 30-minute constant-load cycling exercise, with work rate fixed at 50% of their individual peak workload attained in an incremental exercise test. Ratings of perceived leg muscle pain and perceived exertion were assessed every 5 minutes of exercise. Results: The perceived leg muscle pain was similar (F(1, 10) = 1.18, p = 0.30, ŋ 2 = 0.11) between caffeine (2.1 ± 1.2 arbitrary units) and placebo conditions (2.2 ± 0.9 arbitrary units). The perceived exertion, however, was on average 8 ± 6% lower (F(1, 10) = 12.13; p = 0.006; ŋ 2 = 0.55) during exercise in the caffeine condition (12.4 ± 1.3 arbitrary units) than in the placebo condition (13.1 ± 1.1 arbitrary units). Conclusions: These findings indicate that acute caffeine intake could be an attractive strategy to attenuate the exacerbated perceived exertion of fibromyalgia patients during moderate intensity exercise.